Natural convection in a flexible sided triangular cavity with internal heat generation under the effect of inclined magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi E. (Elsevier Science Bv, 2016)
In this numerical study, magnetohydrodynamics natural convection in a flexible sided triangular cavity with internal heat generation is investigated. The inclined wall of the cavity is cooled and flexible while the left vertical wall is partially heated. Galerkin weighted residual finite element method is used to solve the governing equations. The effects of pertinent parameters such as external Rayleigh number (between 10(4) and 10(6)), internal Rayleigh number (between 10(4) and 10(7)), elastic modulus of flexible wall (between 500 and 10(5)), Hartmann number (between 0 and 40) and inclination angle of the magnetic field (between 0 degrees and 90 degrees) on the fluid flow and heat transfer characteristics were numerically investigated. It was observed local and averaged Nusselt number enhance with external Rayleigh number but in the vicinity of the upper location of the heater local heat transfer deteriorates due to the inclined wall deformation with increasing external Rayleigh number. Heat transfer reduces with internal Rayleigh number and Hartmann number. Averaged heat transfer decreases 13.25% when internal Rayleigh number is increased from 10(4) to 10(7) and decreases 40.56% when Hartmann number is increased from 0 to 10. The reduction in the convection with magnetic field is effective for higher values of external Rayleigh numbers and averaged heat transfer increases with magnetic field inclination angle. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Triangular cavity; Magneto-hydrodynamics; Internal heat generation; Flexible wall; Finite element method